'Candidatus Phytoplasma brasiliense'-related strains associated with papaya bunchy top disease in northern Peru represent a distinct geographic lineage. (February 2017) - Wei, W.; Pérez-López, E.; Davis, R.E.; Bermúdez-Díaz, L.; Granda-Wong, C.; Wang, J.; Zhao, Y.
Abstract: During the 2015–2016 fruit production season, a papaya bunchy top (PBT) disease was observed in a papaya production farm located at Region de Piura, northern Peru. Affected plants exhibited symptoms of excessive proliferation of auxiliary shoots at the top or near top of the main stem, shortening of internodes, leaf yellowing, and necrosis of leaf veins. The symptom syndrome suggested possible infection by a phytoplasma, and the recent discovery of a phytoplasmal disease in a nearby vineyard also indicated that a phytoplasma reservoir and potential vector(s) were present in the area. Molecular diagnostic assays for phytoplasma detection were therefore employed. Nested polymerase chain reactions and subsequent nucleotide sequence analysis confirmed that phytoplasma infection did occur in the papaya production farm. The phytoplasma strains found to be associated with the PBT disease are affiliated with ' Candidatus Phytoplasma brasiliense', a species that had previously never been implicated in a papaya disease anywhere in the world. We provide molecular evidence to suggest that the papaya-infecting phytoplasma strains identified in this study are closely related to a phytoplasma associated with the first grapevine yellows (GY) disease that we recently identified in Peru. The results of our study indicate that these PBT and GY phytoplasma strains in Peru represent an emerging geographic lineage that is distinct from those of all other known ' Ca. Phytoplasma brasiliense' strains in the Americas. Highlights: This is the first documented case of papaya bunchy top disease in northern Peru. The first time ' Candidatus Phytoplasma brasiliense' is implicated in a papaya disease. The Peru papaya bunchy top phytoplasma represents a distinct geographic lineage.